STRATEGI KOMUNIKASI PEMASARAN TERPADU THE KAYON JUNGLE RESORT DALAM MENINGKATKAN BRAND AWARENESS - Aristia Dewi, Putu Ratih; Sugiarica Joni, I Dewa Ayu; Pradipta, Ade Devia (E-Jurnal Medium, 2021)
The Kayon Jungle Resort is a five-star resort located in Payangan District, Gianyar Regency, Bali which has the tagline